Sleep patterns in childhood: a longitudinal assessment from the Generation XXI birth cohort - Marta Gonçalves; Ana Rute Costa; Milton Severo; Ana Henriques; Henrique Barros (Elsevier, 2023)
Objective: To describe sleep-wake patterns in young children, based on sleep characteristics in early infancy and preschool ages, identifying their main sociodemographic characteristics, and to assess the association between different sleep characteristics at both ages. Method: We included 1092 children from the Generation XXI birth cohort, evaluated at six months and four years of age, by face-to-face interviews. Sleep patterns were constructed through latent class analysis and structured equation modeling, including data on wake-up time and bedtime, afternoon naps, locale of nighttime sleep and night awakenings. To estimate the association between sociodemographic characteristics and sleep patterns, odds ratios and 95% confidence intervals were computed using logistic regression. Results: Two sleep patterns were identified through latent class analysis: pattern 1 was characterized by earlier bedtime and wake-up times, while pattern 2 was defined by later times. When compared with pattern 1, pattern 2 was more frequent among children whose mothers had changed from partnered to not partnered until preschool age and those who did not stay at the kindergarten, and was less common among those with siblings. Through structured equation modeling, an aggregating factor was identified at preschool age, which was mainly correlated with bedtime and wake-up time. A positive association between sleep characteristics evaluated in early infancy and in preschool ages was observed. Conclusions: Sleep patterns and circadian sleep preferences seem to be developed early in life, which highlight the importance of promoting an adequate sleep hygiene from infancy, assuming its impact on sleep quality during the life course. Resumen: Objetivo: Describir los patrones de sueño en niños, a partir de las características del sueño en la primera infancia y preescolar, identificando sus características sociodemográficas, y evaluar la asociación entre las características del sueño en ambas edades. Método: Se incluyeron 1092 niños de la cohorte Generación XXI, evaluados a los 6 meses y los 4 años de edad, mediante entrevistas en persona. Los patrones de sueño se identificaron mediante análisis de clases latentes y modelos de ecuaciones estructuradas, utilizando datos sobre la hora de despertarse y acostarse, las siestas de la tarde, el lugar del sueño nocturno y los despertares nocturnos. Para estimar la asociación entre las características sociodemográficas y los patrones de sueño se calcularon odds ratio con intervalos de confianza del 95% mediante regresión logística. Resultados: Se identificaron dos patrones de sueño: el patrón 1 se caracterizó por acostarse y levantarse más temprano; el patrón 2, por tiempos más tardíos. El patrón 2 fue más frecuente entre los niños con madres que cambiaron de pareja a no pareja y que no permanecieron en el jardín de infancia, y menos común entre aquellos con hermanos. Se identificó un factor agregante en la edad preescolar, correlacionado con la hora de acostarse y despertarse. Se observó una asociación positiva entre las características del sueño evaluadas en la primera infancia y en edades preescolares. Conclusiones: Los patrones del sueño parecen desarrollarse temprano en la vida, lo que destaca la importancia de promover una adecuada higiene del sueño desde la infancia.